GL-V9 Promotes Autophagy-Mediated YAP1 Degradation and Activates Mitochondrial Apoptosis in PDAC Cells - Hao Liu; Zhangxing Lin; Yongjian Guo; Yuxin Zhou; Wei Li (MDPI AG, 2024)
Background: Pancreatic ductal adenocarcinoma (PDAC) is among the most aggressive forms of pancreatic cancer with a poor prognosis. YAP1 expression is markedly elevated in PDAC, but how it works is not clear. GL-V9, a derivative of the natural compound wogonin, effectively fights a variety of tumors; however, its effect on PDAC has not yet been studied. Methods: TCGA database analysis, Western blots, immunofluorescence, and real-time PCR were used to evaluate GL-V9's effect on YAP1 expression and mRNA levels. Immunofluorescence was used to examine the co-location of YAP1 with LAMP2 and p62. Co-immunoprecipitation was used to assess the binding of YAP1 to ubiquitin, p62, and TEAD1. A PDAC graft tumor model was used to test GL-V9's pharmacological effects. Western blots and immunohistochemistry were used to measure apoptosis- and autophagy-related protein expression. Results: GL-V9 effectively promoted the degradation of YAP1, reduced YAP1 nuclear localization, and induced mitochondrial apoptosis in PDAC cells. YAP1 overexpression led to the upregulation of Bcl-2 and attenuated the caspase cascade induced by GL-V9. Furthermore, we demonstrated that GL-V9 induced autophagosome-lysosome fusion via the AKT/mTOR/TFEB pathway, leading to mitochondrial apoptosis in PDAC cells. In vivo studies also confirmed that GL-V9 exerts anti-tumor effects by suppressing YAP1 expression, while also activating autophagy and inducing mitochondrial apoptosis in BXPC-3-bearing BALB/c nude mice. Conclusions: Our findings underscore the importance of autophagy-mediated YAP1 degradation in PDAC, providing a novel molecular rationale (GL-V9) as a promising treatment for this disease.